Atypical size and location of a right atrial myxoma: a case report - Singhal, Sushil Kumar; Aiyer, Palash; Grover, Vijay; Gupta, Vijay Kumar (International Surgery Journal, 2017)
Primary intracardiac tumors are rare and approximately 50-55% are myxomas. The majority of myxomas are located in the left atrium. Here We report a case of a large myxoma in the right atrium, which is an uncommon location for this type of tumor who underwent operative intervention with excision of a 9x6 cm multilobulated mass. In this case report, we emphasize the rarity of large myxomas in the right atrium and the difficulty of differential diagnosis given their dimension and location.